The blocking of aquaporin-3 (AQP3) impairs extravillous trophoblast cell migration - Reca, Alejandra Daniela (2018)
Several aquaporins (AQPs) are expressed in extravillous (EVT) and villous trophoblast cells. Among them, AQP3 is the most abundant AQP expressed in chorionic villi samples from first trimester, followed by AQP1 and AQP9. Although AQP3 expression persists in term placentas, it is significantly decreased in placentas from preeclamptic pregnancies. AQP3 is involved in the migration of different cell types, however its role in human placenta is still unknown. Here, we evaluated the role of AQP3 in the migration of EVT cells during early gestation. Our results showed that Swan 71 cells expressed AQP1, AQP3 and AQP9 but only the blocking of AQP3 by CuSO4 or the silencing of its expression by siRNA significantly attenuates EVT cell migration. Our work provides evidence that AQP3 is required for EVT cell migration and suggests that an altered expression of placental AQP3 may produce failures in placentation such as in preeclampsia.